Phytogeographycal data for identifying the climazonal vegetation of the Eastern part of Völgység and Tolnai-hegyhát - Teleki, Balázs (JOURNAL OF LANDSCAPE ECOLOGY, 2012)
This study presents some phytogeographical data to identifying the potential vegetation of the eastern part of Völgység and Tolnai-hegyhát, Hungary. We took floristical survey and represent some characteristic steppeelements. The most important species: Euphorbia glareosa, Euphorbia segueriana, Astragalus austriacus, A. onobrychis, Stipa capillata, Vinca herbacea, Echium italicum, Rapistrum perenne, Thalictrum minus, Taraxacum serotinum. Based on this species we identify the potential vegetation of this area. This is the Aceri tatarici Quercetum Zólyomi 1957.